Valor justo e qualidade da informação contábil: influência da escolha contábil quanto à mensuração das propriedades para investimento - Batista, Fabiano Ferreira (2018)
Measurement of assets at fair value divides evidences related to their impact on quality of accounting information, although they converge with respect to necessary weights for their use: existence of active market, costly information and effect of their recognition in earnings. In this sense, when it comes to non-financial assets, such as Investment Properties (IPs), for which there is no active market, resulting in more subjective estimation, the need for greater attention and debate is reinforced on whether adoption of fair value, in this context, may occur indistinctly or if more caution is required in its adoption. Previous research studies isolated aspects and fails to define which measurement model, historical cost or fair value, results in higher quality information, or which attributes are sacrificed in function of others. In this sense, this work aimed to analyze how the accounting choice regarding the measurement of IPs affects the quality of information, investigating, implicitly, if there was sacrifice of some attribute (s) in function of other (s). Therefore, considering the Brazilian companies that had assets recognized as IPs, between 2010 and 2017, a set of accounting and market attributes was analyzed, consisting of Discretionary Accruals, Conservatism, Opportunity, Relevance, Reliability, Persistence, Predictability and Volatility, using the models proposed by Paulo (2007), Basu (1997), Ball e Shivakumar (2005), Felthan e Ohlson (1995), Kormedi e Lipe (1987) e Francis et al. (2004), respectvely. In general, Reliability and Volatility were observed as the two main links in which the quality information related to the choice of the IPs measurement model is sustained, so that the low reliability of the fair value attributed to the market unavailability the asset itself, to the use of more subjective values obtained through internal valuer, impairs their relevance to investors who discount stock price and causing a gap between earnings and returns. Volatility, on the other hand, impairs the predictability/persistence of earnings, while it may undermine the faithful representation. The relationship between volatility and reliability is justified by the existence of measurement errors and managerial biases, present in the fair value measurements at level 3, which inhibit their predictive capacity, so that the existence of active markets, enabling measurements of fair value at level 1, would be a probable element for improvement predictive capacity, through reliable numbers. Thus, the thesis is defended that Brazilian companies that have assets recognized as PPIs at fair value have lower quality accounting numbers.